Mesin Penjumlah Biner Sederhana - Antonius, Suyanto Edward (PROXIES, 2013)
XOR-gate is a logic gate that is basically built from OR, NAND, and AND gate. As the result, XORgate has its own truth table: its output will be true if its two input has not the same value: true and false or vice versa. This XOR-gate will be the core of binary adder-machine in computer. This research is an experiment analysis of OR, NAND, and AND gate to build the XOR-gate and then implementing this concept in building XOR-gatefrom transistors and resistors. This XOR-gate will be used as a binary-half-adder with two LEDs as the output (binary numbers). At the end of this research, we make a four-bits fuU-adder-machine that is built using IC 74LS83A which has four full-adders inside. Keyword: xor, logic, half-adder,full-adder, IC